Finding Relevant Documents using Top Ranking Sentences : An Evaluation of Two Alternative Schemes - White, Ryen W.; Ruthven, Ian; Jose, Joemon M. (25th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2002), Tampere, Finland., 2002)
In this paper we present an evaluation of techniques that are designed to encourage web searchers to interact more with the results of a web search. Two specific techniques are examined: the presentation of sentences that highly match the searcher’s query and the use of implicit evidence. Implicit evidence is evidence captured from the searcher’s interaction with the retrieval results and is used to automatically update the display. Our evaluation concentrates on the effectiveness and subject perception of these techniques. The results show, with statistical significance, that the techniques are effective and efficient for information seeking.